Statement by The Managing Director on the Work Program of The Executive Board. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2019)
This Work Program translates the strategic directions and policy priorities laid out in the Spring 2019 Global Policy Agenda and the International Monetary and Financial Committee Communique into an Executive Board agenda for the next twelve months. Its main policy priorities and related deliverables are as follows: -- Support domestic policies to enhance resilience and inclusion: -- Upgrade global cooperation to level the playing field and address other shared challenges -- Adapt the Fund's toolkits to lead and support change: -- Continue to modernize the Fund to deliver for the future:.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Policy Priority; Policy Research; Policy; PP; The Fund; United States